2019
DOI: 10.1111/coa.13425
|View full text |Cite
|
Sign up to set email alerts
|

Treating nasal symptoms associated with rhinitis using the intranasal herbal ointment Biyeom‐go: A prospective observational study

Abstract: ObjectivesThe aim of the current study was to investigate the effectiveness and clinical feasibility of Biyeom‐go for the treatment of nasal symptoms associated with rhinitis.DesignProspective observational study.SettingThis study was conducted at the Woosuk Korean Medicine Medical Center in South Korea.ParticipantsFifty‐eight patients with rhinitis participated in this study. All patients received Biyeom‐go treatment >3 times daily for a total of 4 weeks.Main outcome measuresThe primary outcome was the total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The mucosal immune system in humans is poorly studied; however, it has proven to be important in establishing an effective immune response to airborne pathogens and toxic pollutants such as PM, by stimulating Th1/Th2 cells, cytotoxic T lymphocyte production, plasma, and B cells [ 14 ]. It has been found that BYG treatment is beneficial in the management of rhinitis symptoms and rhinitis-associated quality of life by modulating the immune response [ 9 ]. Here, we examined the effects of BYG on immune biomarkers in patients with rhinitis and mice exposed to PM.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mucosal immune system in humans is poorly studied; however, it has proven to be important in establishing an effective immune response to airborne pathogens and toxic pollutants such as PM, by stimulating Th1/Th2 cells, cytotoxic T lymphocyte production, plasma, and B cells [ 14 ]. It has been found that BYG treatment is beneficial in the management of rhinitis symptoms and rhinitis-associated quality of life by modulating the immune response [ 9 ]. Here, we examined the effects of BYG on immune biomarkers in patients with rhinitis and mice exposed to PM.…”
Section: Discussionmentioning
confidence: 99%
“…This prospective observational clinical study was performed at the Woosuk Korean Medicine Medical Center Jeonju-si, Korea, between October 2019 and March 2020. BYG was manufactured by the Dispensary Pharmacy of Woosuk Korean Medicine Medical Center, and the quality was controlled [ 9 ]. Patients were provided with BYG that was used via a cotton swab thrice a day for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[53] Another study reported the effectiveness of Biyeom-go , which is a herbal ointment for rhinitis, is associated with cold-heat pattern and that ointment can be more effective for patients with heat type compared to cold type. [54] Cheonwangbosim-dan , that has been prescribed for insomnia patients, was studied and it improved sleep quality in insomnia patients with a heart- yin deficiency type compared to non-heat- yin deficiency type. [55] It is hard to conclude that herbal medicine using PI is more effective for obesity, above studies can support the possibility of PI for further improvement on treatment of obesity.…”
Section: Discussionmentioning
confidence: 99%